PENERAPAN REWARD AND PUNISHMENT DALAM TEORI BELAJAR BEHAVIORISME - Zamzami, Muh. Rodhi (TA'LIMUNA: Jurnal Pendidikan Islam, 2015)
Behaviorism learning theory has a doctrine that human or animal psychology can be accurately studied only through the examination and analysis of objectively observable and quantifiable behavioral events, in contrast with subjective mental states. In this theory have characteristic at reinforcement on individual behavior, the actualization of reinforcement in behaviorism often use the model of reward and punishment method to give reinforcer on student behavior. The issues were I write in this article, many teachers mistook in use the practice of reward and punishment at reinforcement. Many teachers interpret on the reinforcement practice often by punishment (negative reinforce). The truth reinforcement isn't rewarding and punishment, but it’s the shape to make behavior on a student without the violence. Such, many educators regard as the punishment in learning is still the effective method. The enforcement of the shape the student behavior not must by punishment and reward, but use the continuous stimulus.